Nitric Oxide System and Bronchial Epithelium: More Than a Barrier - Bayarri, María Amparo; Milara, Javier; Estornut, Cristina; Cortijo, Julio (Frontiers in Physiology, 2021)
Airway epithelium forms a physical barrier that protects the lung from the entrance of inhaled allergens, irritants, or microorganisms. This epithelial structure is maintained by tight junctions, adherens junctions and desmosomes that prevent the diffusion of soluble mediators or proteins between apical and basolateral cell surfaces. This apical junctional complex also participates in several signaling pathways involved in gene expression, cell proliferation and cell differentiation. In addition, the airway epithelium can produce chemokines and cytokines that trigger the activation of the immune response. Disruption of this complex by some inflammatory, profibrotic, and carcinogens agents can provoke epithelial barrier dysfunction that not only contributes to an increase of viral and bacterial infection, but also alters the normal function of epithelial cells provoking several lung diseases such as asthma, chronic obstructive pulmonary disease (COPD), cystic fibrosis (CF) or lung cancer, among others. While nitric oxide (NO) molecular pathway has been linked with endothelial function, less is known about the role of the NO system on the bronchial epithelium and airway epithelial cells function in physiological and different pathologic scenarios. Several data indicate that the fraction of exhaled nitric oxide (FENO) is altered in lung diseases such as asthma, COPD, lung fibrosis, and cancer among others, and that reactive oxygen species mediate uncoupling NO to promote the increase of peroxynitrite levels, thus inducing bronchial epithelial barrier dysfunction. Furthermore, iNOS and the intracellular pathway sGC-cGMP-PKG are dysregulated in bronchial epithelial cells from patients with lung inflammation, fibrosis, and malignancies which represents an attractive drug molecular target. In this review we describe in detail current knowledge of the effect of NOS-NO-GC-cGMP-PKG pathway activation and disruption in bronchial epithelial cells barrier integrity and its contribution in different lung diseases, focusing on bronchial epithelial cell permeability, inflammation, transformation, migration, apoptosis/necrosis, and proliferation, as well as the specific NO molecular pathways involved.